Analysis of Cultural Communication and Public Perceptions of Traditional Parafu Medicine in Bima from an Islamic Perspective - Anggun Hidayah Putri; Sukarta; Suhadah; Badlihisham Mohd Nasir (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
Traditional Parafu medicine in Diha Village, Bima, represents a cultural practice with strong historical, social, spiritual, and religious significance. This practice is not only part of the community’s identity but also serves as a form of cultural communication that transmits ancestral values and social norms. This study aims to analyze the relationship between cultural communication, religious values, and public perceptions of Parafu practices. A qualitative approach was employed, with data collected through semi-structured interviews with six key informants, including traditional leaders, religious figures, community representatives, and healthcare practitioners, complemented by participatory observation. Data were analyzed thematically to identify patterns of communication, empirical experiences, and socio-spiritual values underlying Parafu practices. The findings reveal that Parafu rituals, such as prayers, bathing in sacred wells, and communal meals, symbolize togetherness and reflect the harmony between cultural values and Islamic principles, where healing is believed to come from Allah SWT. Variations in understanding of sacred locations indicate diverse interpretations within the community. The study confirms that cultural communication, empirical experience, and socio-spiritual values form a strong foundation for sustaining Parafu practices. Moreover, the findings support the preservation of cultural heritage, strengthening of community identity, and the design of health communication strategies that respect local cultural norms and Islamic principles, ensuring the continued relevance of Parafu practices in the modern era.